Desymmetrization strategy to achieve triptycene-based 3,6-dimethoxytriphenylenes via oxidative cyclodehydrogenation - Reinhard, Dennis; Rominger, Frank; Mastalerz, Michael (European journal of organic chemistry, 2020)
A desymmetrization strategy has been developed to achieve a triptycene-based hexamethoxy tris triphenylene in high yields by taking into account the regioselectivity of the Scholl-type oxidative cyclodehydrogenation governed by methoxy groups. Different routes starting from D3h- and C3v-symmetric precursors have been compared as well as by Mallory-type photocyclizations.